PELAKSANAAN BUDAYA HUKUM HAKIM DAN ADVOKAT DALAM KAITANNYA DENGAN PENEGAKAN HUKUM - Hulman Panjaitan (to-ra, 2017)
Abstract Legal culture is a very important element and priority is a concern in relation to law enforcement, That’s not limited to the implementation of the legal culture of judges and advocates as part of law enforcement. The execu- tion and implementation of the legal culture of each law enforcement apparatus, including judges and advocates have not become a serious concern. What has become a code of ethics as a guideline for behaving for judges and advocates has not inspired and integrated in the life and behavior of a judge and advocate in carrying out their duties and responsibilities. Therefore, for enforcement of the law and justice, presumably this legal culture as one of the most important elements in the legal system must befully applied and implemented by each law enforcement apparatus. Keywords: the legal culture; judges and advocates; law enforcement.